Manual of structural kinesiology - Floyd, R. T. (McGraw Hill LLC, 2024)
Manual of Structural Kinesiology, 22e provides a straightforward view of human anatomy and its relation to movement. While the manual is designed for use in undergraduate structural kinesiology courses, other clinicians and educators will also benefit from the text. The manual clearly identifies specific muscles and muscle groups and describes exercises for strengthening and developing those muscles. The author’s goal continues to be to provide important information in an accessible format through a combination of logical presentation, extensive and clear illustrations, and concise writing style.